The Minimum Data Set 3.0 Cognitive Function Scale - Thomas, Kali S; Dosa, David; Wysocki, Andrea; Mor, Vincent (Medical care, 2017)
The Minimum Data Set (MDS) 3.0 introduced the Brief Interview for Mental Status (BIMS), a short performance-based cognitive screener for nursing home (NH) residents. Not all residents are able to complete the BIMS and are consequently assessed by staff. We designed a Cognitive Function Scale (CFS) integrating self-report and staff-report data and present evidence of the scale's construct validity. A retrospective cohort study. The subjects consisted of 3 cohorts: (1) long-stay NH residents (N=941,077) and (2) new admissions (N=2,066,580) during 2011-2012, and (3) residents with the older MDS 2.0 assessment in 2010 and the newer MDS 3.0 assessment (n=688,511). MDS 3.0 items were used to create a single, integrated 4-category hierarchical CFS that was compared with residents' prior MDS 2.0 Cognitive Performance Scale scores and other concurrent MDS 3.0 measures of construct validity. The new CFS suggests that 28% of the long-stay cohort in 2011-2012 were cognitively intact, 22% were mildly impaired, 33% were moderately impaired, and 17% were severely impaired. For the admission cohort, the CFS noted 56% as cognitively intact, 23% as mildly impaired, 17% as moderately impaired, and 4% as severely impaired. The CFS corresponded closely with residents' prior MDS 2.0 Cognitive Performance Scale scores and with performance of Activities of Daily Living, and nurses' judgments of function and behavior in both the admission and long-stay cohorts. The new CFS is valuable to researchers as it provides a single, integrated measure of NH residents' cognitive function, regardless of the mode of assessment.